Rapid development of mobile apps using App Inventor and AGCO API - Kepley, Spencer (Kansas State University, 2014)
Mobile apps are useful tools for many different purposes. In agriculture, apps can be used to check the weather and markets, control irrigation, and monitor machine activity among other uses. This research project is a collaboration between Kansas State University and AGCO and includes the development of two apps, using MIT Application Inventor and Google App Engine. Kansas State University was responsible for developing the apps user interface and functionality while AGCO provide the data needs for the apps through Google App Engine. The first app is called Crop Maturity App and measures Growing Degree Days from a crops planting date. The second app is called Combine Efficiency App and determines the performance of a combine harvesting based on its speed. AGCO provided the server support for these apps from a weather service and their own combines that are connected. This project demonstrates the possibility of an open-source development environment with AGCO machine data.
Keywords: App development; App Inventor; AGCO API; Open source programming; Agriculture, General (0473); Computer Science (0984); Engineering, Agricultural (0539)